Analisis Hukum Perjudian Togel di Wilayah Hukum Polres Indramayu: Perspektif Hukum Positif - Sukenda, Sukenda (CV. Strata Persada Academia, 2024)
Efforts to combat gambling crimes can be carried out in practice through preemptive measures, widespread public awareness campaigns, preventive actions (before the occurrence of any gambling crime), and repressive actions to enforce the law against individuals engaged in gambling activities. These three prevention efforts are interdependent and form an inseparable chain in combating criminal activities in general, including specifically Togel gambling crimes. How does the Indramayu Police Resort undertake efforts to prevent Togel gambling crimes from a positive legal perspective? In this research, the author employs a normative method. In legal studies, the normative method refers to an approach that focuses on determining what